Hungarian Monitoring, 19 June 1989 . [Magyar rádiófigyelő], 1989. június 19 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Czechoslovakia takes negative view of what happened at funeral of Imre Nagy and colleagues - Yesterday's elections in Poland - European Parliamentary elections - Situation in Beijing - START talks recommence in Geneva Domestic Affairs: - Following official Bucharest protest to Hungary, workers' meetings held throughout Romania - No reaction yet from Hungarian government to Romanian accusations following Nagy's funeral - More Hungarian organizations make statements following Viktor Orbán's speech on Heroes' Square - Rehabilitation of 90 ministers of Hungarian Calvinist church Külpolitika: - Csehszlovákiában negatívan ítélik azt, ami Nagy Imre és társainak temetésén lezajlott - A tegnapi lengyel választások - Az Európa Parlament választások - Pekingi helyzetkép - Genfben felújítják a START tárgyalásokat Belpolitika: - A Magyarországnak küldött hivatalos bukaresti tiltakozás után egész Romániában munkásgyűléseket tartottak - A magyar kormány egyenlőre nem reagál a Nagy Imre temetést követő román vádakra - Orbán Viktor Hősök-téri beszéde kapcsán több magyar szervezet is nyilatkozatot tett - A magyarországi református egyház 90 lelkészének rehabilitása